(untitled) (MIST International Journal of Science and Technology, 2023)
Wire arc additive manufacturing (WAAM) is one of the less-explored metal 3D printing technologies that hold up a huge potential for large-scale product manufacturing across multiple industries. The low-cost AM uses arc energy as a heat source and metallic wire as a feedstock material. The process is sustainable and supports green manufacturing. However, the major challenge associated with the WAAM is that heat management leads to the development of residual stress causing dimensional inaccuracy and poor surface finish. Therefore, fourlayer straight wall structures are fabricated by depositing material layer-uponlayer with nine distinct heat inputs (HI). The prime focus of the work is to study the effect of HI on the dimensional accuracy and the quality of deposited structures. The influence of deposition height on the surface topography is investigated. Furthermore, the effect of HI on the mechanical properties of the WAAM-printed thin wall is examined. The results show that with increase in the number of depositing layers, surface roughness values get increased under the similar process parameter used for the part fabrication. Therefore, it is recommended to re-adjust the process parameter after certain layers of deposition with proper monitoring of the thermal condition in the deposited layers while fabricating medium to large WAAM components. The outcomes from the studies show that increases in the HI while fabricating the WAAM component deteriorates the surface quality of the deposited layer and are responsible for reducing the mechanical properties of the WAAM-printed component. MIJST, Vol. 11, June 2023 : 11-20 DOI: https://doi.org/10.47981/j.mijst.11(01)2023.419(11-20)